Effect of "the Awakening Protocol" in the outcome of liver transplantation - Lima,Agnaldo Soares (2013)
PURPOSE: To analyze mortality (7 days) or graft loss in liver transplantation (Tx) performed within the Awakening Protocol (AP) compared to sequential Tx. METHODS: Analysis of 243 liver tx (230 patients), divided into sequential tx or PD (early morning) to compare graft loss or death (7 days). Significant differences at p <0.05 RESULTS: The PD was adopted in 32.5% of tx. The cold ischemia time (p <0.01) and the interval until transplantation (p <0.01) were significantly different. Age of the donor and recipient, Donor Risk Index, MELD score, and donor base excess, sodium, creatinine and glucose were not different between groups. Previous abdominal surgery was a risk factor for early mortality, but was equally distributed between the groups. There was no difference in mortality or graft loss within 7 days (p = 0.521) CONCLUSION: The adoption of PD, to start tx the morning when harvesting occurs after 10p.m. did not result in worse patient and graft survival. Transplant patients with fulminant hepatic failure and high-risk grafts do not apply to this surgical tactics.